Preparation of chitosan nanoparticles as Ginkgo Biloba extract carrier: In vitro neuroprotective effect on oxidative stress-induced human neuroblastoma cells (SH-SY5Y)* - Karavelioglu, Zeynep; Cakir-Koc, Rabia (ELSEVIER, 2021)
Ginkgo biloba (Gb) is an ancient Chinese tree cultivated for its health-promoting properties. Moreover, Gb extract has a therapeutic effect, especially on neurodegenerative diseases. In this study, Gb extract-loaded chitosan nanoparticles (Gb-CsNPs) were synthesized by ionic gelation method. Size and zeta potential of the nanoparticles were analyzed and Scanning Electron Microscopy (SEM) and Fourier Transform Spectroscopy (FT-IR) were performed. Besides, encapsulation efficacy and loading capacity were calculated, and in vitro release, and cellular uptake studies were carried out. The biocompatibility of Gb-CsNPs was demonstrated and their neuroprotective activity was investigated on oxidative stress-induced SH-SY5Y cells. Apoptotic cells were monitored by DAPI, and cell migration was examined by in vitro scratch assay. Results showed that Gb-CsNPs had an average size of 104.4 nm, their zeta potential and polydispersity index (PDI) values were 29.3 mV, and 0.09 respectively. Encapsulation efficacy and loading capacity were found as 97.4% and 40%, respectively. It has been revealed that Gb-CsNPs were biocompatible and showed neuroprotective activity by increasing cell viability from 60% to 92.3%. Consequently, neuroprotective effect of the Gb extract was increased by chitosan encapsulation. This formulation is a candidate to be used as a food supplement after being supported by future in vivo studies.
Keywords: Ginkgo biloba extract; Chitosan nanoparticles; Neuroprotection; SH-SY5Y cells; DELIVERY; Biochemistry & Molecular Biology; Chemistry; Polymer Science